2022
DOI: 10.1371/journal.pgph.0000132
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors influencing utilization of HIV prevention and treatment services among patients and providers in a heterogeneous setting: A qualitative study from South Africa

Abstract: Despite advances made in HIV prevention and treatment interventions in South Africa, barriers to their utilization continue to exist. Understanding perspectives from patients and providers of healthcare can shed light on the necessary strategies to enhance uptake of HIV services. A cross-sectional qualitative study was conducted in July 2020 in Ekurhuleni District. Based on HIV prevalence estimates from a national survey, male condom use coverage and antiretroviral treatment (ART) initiation rates from routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Anticipated stigma typically refers to expectations of prejudice or discrimination in health services, while internalized stigma typically refers to one's own belief in negative ideas around one's stigmatized identity [21]. Recent work continues to highlight how such forms of stigma create barriers towards linkage to health services [24,25], and lead to difficulties among patients in sustaining their engagement in HIV health services [26][27][28].…”
Section: Individualistic Manifestations Of Stigmamentioning
confidence: 99%
“…Anticipated stigma typically refers to expectations of prejudice or discrimination in health services, while internalized stigma typically refers to one's own belief in negative ideas around one's stigmatized identity [21]. Recent work continues to highlight how such forms of stigma create barriers towards linkage to health services [24,25], and lead to difficulties among patients in sustaining their engagement in HIV health services [26][27][28].…”
Section: Individualistic Manifestations Of Stigmamentioning
confidence: 99%
“…This case would assist in knowledge sharing and adherence if information about PEP was already publicised. Although the more significant majority completed the course of the PEP treatment, a high number of HCPs does not finish treatment because of several reasons that are somewhat justified (Aigbodion et al 2019 ; Bareki & Tenego 2018 ; Makhado & Seekane 2020 ; Ncube et al 2014 ; Sultan et al 2014 ; Chimoyi et al 2022 ). The ill knowledge of PEP procedures shows the importance of follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Various studies have identified and documented barriers to engagement in HIV care, including medication side effects, complexity of dosing schedules, low patient education level, poverty, stigma, distance and transportation challenges, quality of care received and reliance on traditional medicines. [10][11][12][13] However, one potential barrier to continuous engagement in HIV care and treatment that is gaining attention is the mobility of people between regions and countries. 7 14 15 In 2011, UNAIDS and the International Organization for Migration, signed an agreement recognising HIV-related challenges faced by mobile populations with objectives to integrate human rights and the needs of mobile populations into national and regional HIV responses and to ensure universal access to HIV prevention, treatment, care and support.…”
Section: Introductionmentioning
confidence: 99%